(untitled) (Research, Society and Development, 2022)
Bioactive packaging with antioxidant action helps to maintain the sensory and nutritional characteristics of foods rich in lipids. This review presents studies on the use of these packages to minimize losses and extend the shelf life of these products. Several compounds with antioxidant action (plant extracts and essential oils) can be used for this purpose, among them, the use of natural compounds has emerged as a potential alternative to meet the desires of consumers. Studies have shown an interesting prospect for the application of active antioxidant packaging to maintain the quality of these foods. A new trend also stands out in the context of sustainable development, with the production of active packaging from bio-based polymers. However, there is an urgent need for further studies on this subject aiming at the production of packaging with adequate techno-functional, mechanical, and thermal properties for production on an industrial scale in order to replace conventional packaging.